Non-ischemic cerebral enhancing lesions after intracranial aneurysm endovascular repair: a retrospective French national registry. (20th September 2021) - Shotar, Eimad; Labeyrie, Marc-Antoine; Biondi, Alessandra; Velasco, Stéphane; Saliou, Guillaume; Boulouis, Grégoire; Daumas-Duport, Benjamin; Bourcier, Romain; Janot, Kevin; Herbreteau, Denis; Michelozzi, Caterina; Premat, Kevin; et al.
Abstract : Background: Non-ischemic cerebral enhancing (NICE) lesions are exceptionally rare following aneurysm endovascular therapy (EVT). Objective: To investigate the presenting features and longitudinal follow-up of patients with NICE lesions following aneurysm EVT. Methods: Patients included in a retrospective national multicentre inception cohort were analysed. NICE lesions were defined, using MRI, as delayed onset punctate, nodular or annular foci enhancements with peri-lesion edema, distributed in the vascular territory of the aneurysm EVT, with no other confounding disease. Results: From a pool of 58 815 aneurysm endovascular treatment procedures during the study sampling period (2006–2019), 21/37 centres identified 31 patients with 32 aneurysms of the anterior circulation who developed NICE lesions (mean age 45±10 years). Mean delay to diagnosis was 5±9 months, with onset occurring a month or less after the index EVT procedure in 10 out of 31 patients (32%). NICE lesions were symptomatic at time of onset in 23 of 31 patients (74%). After a mean follow-up of 25±26 months, 25 patients (81%) were asymptomatic or minimally symptomatic without disability (modified Rankin Scale (mRS) score 0–1) at last follow-up while 4 (13%) presented with mild disability (mRS score 2). Clinical follow-up data were unavailable for two patients. Follow-up MRI (available in 27 patients; mean time interval after onset of 22±22 months) demonstrated persistent enhancement in 71% of cases. Conclusions: The clinical spectrum of NICE lesions following aneurysm EVT therapy spans a wide range of neurological symptoms. Clinical course is most commonly benign, although persistent long-term enhancement is frequent.